1995
DOI: 10.1159/000120949
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Complications of Hydrocephalus

Abstract: Problems may still occur for patients treated for infantile hydrocephalus who graduate to become adults, including unsatisfactory follow-up. We have continued the supervision in an adult institution of 70 children originally treated in the Birmingham Children’s Hospital between 1974 and 1978. In these patients, 33 (16.4%) of a total of 201 shunt revision procedures and 5 of the 8 subtemporal decompressions for slit ventricle syndrome were performed after the age of 16 years. Similarly, 7 shunt infections occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…11,12,16,17 Data from the Norwegian background population show that 81% males and 77% females in their 40s are living with a partner. The poor partnering (relationship) rate of 35% in our cohort is lower than expected.…”
Section: Social Outcomementioning
confidence: 99%
“…11,12,16,17 Data from the Norwegian background population show that 81% males and 77% females in their 40s are living with a partner. The poor partnering (relationship) rate of 35% in our cohort is lower than expected.…”
Section: Social Outcomementioning
confidence: 99%
“…Abdominal pseudocyst formation with signs of shunt malfunction and/or abdominal symptoms is very infrequent, but they are important complications. [2][3][4][5][6] In the literature, the incidence of the formation of CSF pseudocyst ranged between 2 and 5%. Rainov described an incidence of 4.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is the preferential method, it is not free from complications. [1][2][3] Abdominal pseudocyst formation is an infrequent complication and is characterized with signs of shunt malfunction and/or abdominal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…There were 4 sudden deaths in the community suspected to have been due to shunt failure. Sgouros et al 75 reported the adulthood experiences of 70 patients followed from childhood for congenital hydrocephalus, including 23 with myelomeningocele. Thirty-three of 201 shunt revisions and 5 of 8 subtemporal decompressions were required after the age of 16 years.…”
Section: Hydrocephalusmentioning
confidence: 99%